Knowing and teaching kinaesthetic experience in skateboarding: an example of sensory emplacement - Bäckström, A. (Sport, Education and Society, 2014)
The body has become a vital research object in several disciplines in recent years. Indeed, in the social sciences and humanities, a corporeal turn in which embodiment has become a key concept related to learning and socialisation is discussed. This cross-disciplinary paper addresses the epistemological question of how we know what we know and theoretically and empirically contributes to current arguments of a shift from embodiment to emplacement. In other words, this study strives for understanding of the intersection of mind, body and place through a focus on how bodily knowing is formed as part of a moving world. The purpose of the paper is to explore the kinaesthetic experience as bodily knowing in emplaced semi-formal teaching. Through long-term ethnography in a Swedish skateboard setting and in-depth analysis of digital visual material, this paper demonstrates how kinaesthetic experience might be viewed as knowing and how a particular type of this experience might be interpreted as explosiveness and, as such, an act of physical remembrance and energy transformation. Knowing is formed along paths of movement and rhythm, and kinaesthesia is identified as a multisensory experience. It is argued that a fruitful way of bridging the mind-body divide is to view the body as un/knowing, rendering it both knowing and not knowing simultaneously. Moreover, emplaced via its senses in a sociocultural and spatio-temporal environment, this conceptualisation of a moving body in a moving world might allow for re-thinking regarding how a body in context knows, teaches and, possibly, learns.